Saturday night at the Lakeside Supper Club : [large type] a novel - Stradal, J. Ryan (Random House Large Print, 2023)
"This novel is the story of Mariel and Ned, a couple from two very different restaurant families in rustic Minnesota, and the legacy of love and tragedy, of hardship and hope, that unites and divides them"--